Coping with Neologisms in English / Arabic Translation - Hameed, Sinan Gailan (2009)
A Master of Arts Thesis in Translation Submitted to the College of Arts and Sciences by Sinan Gailan Hameed Entitled, "Coping with Neologisms in English / Arabic Translation" April 2009. Available are both Hard and Soft Copies of the Thesis.